NLRP3-like protein negatively regulates the expression of antimicrobial peptides in Penaeus vannamei hemocyates - Zhihong Zheng (Elsevier, 2021)
NACHT, LRR and PYD domains-containing protein 3 (NLRP3) protein is the core actor involved in inflammasome formation, and plays a pivotal role in the innate immune response. However, whether NLRP3 participates in the regulation of innate immunity in invertebrates is still unknown. In the present study, we characterized a NLRP3 ortholog in Penaeus vannamei (designated PvNLRP3-like) with 2514 bp length of open reading frame (ORF) encoding a putative protein of 837 amino acids. Sequence analysis revealed that PvNLRP3-like contained only NACHT domain and shared closely homology with other invertebrates, but the topological structure of NACHT domain of PvNLRP3-like is similar with that in human NLRP3. PvNLRP3-like was ubiquitously expressed in tissues and induced in hemocytes by Vibrio parahaemolyticus, Streptococcus iniae and White Spot Syndrome Virus (WSSV) challenge, suggesting that PvNLRP3-like participated in the immune responses to pathogens. Furthermore, silencing of PvNLRP3-like followed by V. parahaemolyticus stimulation negatively regulated the transcripts of antimicrobial peptides (AMPs) including Lysozyme (LYZ) 3, Crustin (CRU) 2, Anti-lipopolysaccharide factor (ALF) 2/3 and Penaeidins (PEN) 3/4. This study enriches our current knowledge on shrimp innate immunity, and provides novel perspective to understand the immune regulation role of PvNLRP3-like.